Electrochemical Study for the Effect of Simvastatin and Atorvastatin on Coenzyme Q10 by Differential Pulse Polarography Using Mercury Drop Electrode - A. Alasaddy, Sahil (Iraqi Journal of Science, 2023)
Statin drugs act by inhibiting the enzyme HMG-CoA reductase which is responsible for manufacture of cholesterol and the biosynthesis essential energy production Co-factor (Coenzyme Q10). The aim from this research includes study the effect of statin drugs (Simvastatin and Atorvastatin) on the Coenzyme Q10 using differential pulse polarographic technique at a dropping mercury electrode (DME) and in a mixture of [4:1] methanol-phosphate buffer of pH7.0 as supporting an electrolyte. Prior to this, the behaviors of Simvastatin, Atorvastatin and Coenzyme Q10 were studied separately in their solvents. The half-wave potential (E1/2) of Co Q10 were -0.31volt and -1.37Volt, -1.33 Volt for simvastatin and atorvastatin respectively. A mixture of Coenzyme Q10 with Simvastatin and Atorvastatin in the same solvent shows a shift in their peak potential (Ep) toward more negative potentials values by (-0.06volt) for Simvastatin and by (-0.09volt) by Atorvastatin.